TRACTOR PAINT QUALITY CONTROL BY INTEGRATING THE SIX SIGMA METHOD AND FAIL MODE AND EFFECT ANALYSIS (FMEA) PT. XYZ - Setiawan, Ardhi Wahyu; Sulistiyowati, Wiwik; Jakaria, Ribangun Bamban; Sukmono, Tedjo (Journal for Technology and Science, 2025)
Objective: The aim of this research is to find out the main factors that cause defects in painting parts and make appropriate suggestions/improvements to reduce and prevent defects in the painting process. Methods: The Method employed is that The method used is the Six Sigma method and the FMEA (Failure Mode Effect and Analysis) method. Six Sigma in technical methods is oriented towards a statistical approach to calculating product defects. The goal is to reduce process variance by eliminating defects that interfere with customer satisfaction. FMEA is a technical analysis which, if carried out correctly and at the right time, will provide great value in helping the decision making process. Results: The Results show that The research results show that the average DPMO value for tractor product production on weekdays from January 1 2023 to April 30 2023 is 107618.46 with an average sigma value of 2.74. Novelty: The recommendation for improvement from the FMEA method is that the cause of the defect with the highest RPN value is painting that does not comply with the SOP of 576. The proposed improvement for the cause of this defect is supervision of painting employees. The Novelty is derived from the specific application and findings of the Six Sigma and FMEA methods in addressing the painting defects at PT. XYZ.